Labour supply and taxation - Costas Meghir; David Phillips (Institute for Fiscal Studies (IFS), 2008)
In this paper we provide an overview of the literature relating labour supply to taxes and welfare benefits with a focus on presenting the empirical consensus. We begin with a basic continuous hours model, where individuals have completely free choice over their hours of work. We then consider fixed costs of work, the complications introduced by the benefits system, dynamic aspects of labour supply and we place the analysis in the context of the family. The key conclusion of this work is that in order to estimate the impact of tax reform and be able to generalise results, a structural approach that takes account of many of these issues is desirable. We then discuss the 'new Tax Responsiveness' literature which uses the response of taxable income to the marginal tax rate as a summary statistic of the behavioural response to taxation. Underlying this approach is the unsatisfactory nature of using hours as a proxy for labour effort for those with high levels of autonomy on the job and who already work long hours, such as the self employed or senior executives. After discussing relevant theory we then provide a summary of empirical estimates and the methodology underlying the studies. Our conclusion is that hours of work are relatively inelastic for men, but are a little more responsive for married women and lone mothers. On the other hand, participation is quite sensitive to taxation and benefits for women. Within this paper we present new estimates form a discrete participation model for both married and single men based on the numerous reforms over the past two decades in the UK. We find that the participation of low education men is somewhat more responsive to incentives than previously thought. For men with high levels of education, participation is virtually unresponsive; here the literature on taxable income suggests that there may be significant welfare costs of taxation, although much of this seems to be a result of shifting income and consumption to non-taxable forms as opposed to actual reductions in work effort.
Keywords: J22; H24; H31; 330; Labour Supply; Income taxation; Welfare Benefits; Tax Credits; Incentive Effects; Arbeitsangebot; Männer; Frauen; Steuersystem; Steuerreform; Theorie; Großbritannien